Viscoelastic testing in oncology patients (including for the diagnosis of fibrinolysis): Review of existing evidence, technology comparison, and clinical utility. (22nd October 2020) - Walsh, Mark; Kwaan, Hau; McCauley, Ross; Marsee, Mathew; Speybroeck, Jacob; Thomas, Scott; Hatch, Jordan; Vande Lune, Stefani; Grisoli, Anne; Wadsworth, Sarah; Shariff, Faisal; Aversa, John G.; et al.
Abstract: The quantification of the coagulopathic state associated with oncologic and hematologic diseases is imperfectly assessed by common coagulation tests such as prothrombin time, activated partial thromboplastin time, fibrinogen levels, and platelet count. These tests provide a static representation of a component of hemostatic integrity, presenting an incomplete picture of coagulation in these patients. Viscoelastic tests (VETs), such as rotational thromboelastometry (ROTEM) and thromboelastography (TEG), as whole blood analyses, provide data related to the cumulative effects of blood components and all stages of the coagulation and fibrinolytic processes. The utility of VETs has been demonstrated since the late 1960s in guiding blood component therapy for patients undergoing liver transplantation. Since then, the scope of viscoelastic testing has expanded to become routinely used for cardiac surgery, obstetrics, and trauma. In the past decade, VETs' expanded usage has been most significant in trauma resuscitation. However, use of VETs for patients with malignancy‐associated coagulopathy (MAC) and hematologic malignancies is increasing. For the purposes of this narrative review, we discuss the similarities between trauma‐induced coagulopathy (TIC) and MAC. These similarities center on the thrombomodulin‐thrombin complex as it switches between the thrombin‐activatable fibrinolysis inhibitor coagulation pathway and activating the protein C anticoagulation pathway. This produces a spectrum of coagulopathy and fibrinolytic alterations ranging from shutdown to hyperfibrinolysis that are common to TIC, MAC, and hematologic malignancies. There is expanding literature regarding the utility of TEG and ROTEM to describe the hemostatic integrity of patients with oncologic and hematologic conditions, which we review here.